2022
DOI: 10.1186/s12951-022-01288-x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable MoSe2-polyvinylpyrrolidone nanoparticles with multi-enzyme activity for ameliorating acute pancreatitis

Abstract: Exogenous antioxidant materials mimicking endogenous antioxidant systems are commonly used for the treatment of oxidative stress-induced injuries. Thus, artificial enzymes have emerged as promising candidates for balancing and treating the dysregulation of redox homeostasis in vivo. Herein, a one-pot hydrothermal strategy for the facile preparation of MoSe2-polyvinylpyrrolidone (PVP) nanoparticles (NPs) is reported. The synthesized NPs were biodegradable due to their exposure to oxygen and exhibited high stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…[67][68][69] Hu et al reported that a polyvinylpyrrolidone-stabilized MoSe 2 nanoparticle (MoSe 2 -PVP NPs) could be easily prepared. 70 The MoSe 2 -PVP NPs effectively simulates various natural enzymes, and eliminates free radicals such as •OH, •O 2 − and 3-ethylbenzothiazoline-6-sulfonic acid. MoSe2-PVP NPs significantly increased the survival probability of cells in H 2 O 2 and had a significant protective effect on AP animal models.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…[67][68][69] Hu et al reported that a polyvinylpyrrolidone-stabilized MoSe 2 nanoparticle (MoSe 2 -PVP NPs) could be easily prepared. 70 The MoSe 2 -PVP NPs effectively simulates various natural enzymes, and eliminates free radicals such as •OH, •O 2 − and 3-ethylbenzothiazoline-6-sulfonic acid. MoSe2-PVP NPs significantly increased the survival probability of cells in H 2 O 2 and had a significant protective effect on AP animal models.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…MoSe2-PVP NPs significantly increased the survival probability of cells in H 2 O 2 and had a significant protective effect on AP animal models. 70 Another example, Prussian blue, as an ancient dye, is a clinical antidote for radioactive element poisoning such as thallium. Prussian blue nanoparticles (PB…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…In normal organisms, the antioxidant enzyme system requires the participation of multiple enzymes to maintain redox homeostasis in cells. To simulate this multi-enzyme complex system, we prepared polyvinylpyrrolidone-modified molybdenum selenide nanoparticles (MoSe 2 -PVP NPs) by a hydrothermal one-pot method for the treatment of AP [ 115 ]. MoSe 2 -PVP NPs were prepared simply and efficiently, which exhibited good colloidal stability, biocompatibility, and biodegradability, and mimicked the activities of native CAT, SOD, POD, and GPx.…”
Section: Antioxidant Nanomaterials For Apmentioning
confidence: 99%
“…( d ) Histogram of apoptosis and necrosis in untreated and MoSe 2 -PVP NPs-treated RAW264.7 cells ( e ) of cell apoptosis and necrosis distribution in untreated and MoSe 2 -PVP NPs-treated RAW264.7 cells. *** p < 0.001, Representative graphics are shown, Reprinted from [ 115 ]. Copyright 2022.…”
Section: Figures Scheme and Tablesmentioning
confidence: 99%
“…Specifically, this ability has a significant impact on the kinetics of polymerization of HEMA in the presence of PVP (through the formation stage of a complex with charge transfer) and the formation of the polymer matrix structure [ 42 ]. At the same time, the use of PVP opens up additional opportunities for modification of various substances [ 43 , 44 ] and improvement of technologies for obtaining new functional materials with a set of unique properties [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%